Meta-Analysis Study: Correlation Study of the Influence of Motivation on Student Learning Outcomes - Zulyusri; Ida Elfira; Violita Violita; Tomi Apra Santosa (Pusat Riset dan Inovasi Nasional, 2022)
This study intends to investigate the relationship between motivation and student learning outcomes. Impact measures in several studies that examined the relationship between the influence of motivation on student learning outcomes were analyzed using a meta-analysis procedure. Empirical data were collected using electronic search engines such as Google Scholar, Garuda Portal, and national journal URLs. The effect size is used as a starting point for data analysis. A systematic review of research findings in Indonesia's national e-journal was used, with 18 articles selected as a sample that met the criteria. The results of calculating the combined effect size obtained a p-value of less than 0.001 and an estimated value of 0.825. A meta-analysis study found that motivation and learning outcomes had a significant relationship, with the strength of the relationship in the high category. The variance of the studies analyzed is also very high, with I2 test results far exceeding 50%, implying that this study is heterogeneous, with a significant estimate value in the SMK subgroup category (estimated value 1,031) with a p-value of 0.001 and the SMP subgroup (estimated value 1.186) with a p-value of 0.005.